PENGARUH JOB SATISFACTION, PERCEIVED ORGANIZATIONAL SUPPORT, WORK-LIFE BALANCE DAN JOB STRESS TERHADAP TURNOVER INTENTION PADA PT. TRIKUSUMA JAYA PERKASA SEMARANG - Aisyatul, Umi; Rauly Sijabat; Rita Meiriyanti (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of job satisfaction, perceived organizational support, work-life balance and job stress on turnover intention in PT. Trikusuma Jaya Perkasa Semarang. This study used quantitative research methods. The population used in the study was employees of PT. Trikusuma Jaya Perkasa employees and the sample used was 81 employees of PT. Trikusuma Jaya Perkasa employees using probability sampling Data analysis in the study using SPSS for window software version 26. The results of this study show that there is a negative influence between job satisfaction (X1) on turnover intention at PT. Trikusuma Jaya Perkasa Semarang (Y) partially with a calculated t-value of -0.344 and a significance value of 0.678. Perceived organizational support (X2) has a positive and significant effect on PT. Trikusuma Jaya Perkasa Semarang (Y) partially with a calculated t value of 2,304 significance value of 0.024. Work-life balance (X3) negatively affects turnover intention in PT. Trikusuma Jaya Perkasa Semarang (Y) partially with a calculated t value of -.465 and a significance value of 0.664. Job stress (X4) has no effect on turnover intention in PT. Trikusuma Jaya Perkasa Semarang (Y) partially with a calculated t value of -0.622 and a significance value of 0.535.